Stability of papain in aqueous organic solvent by reverse phase liquid chromatography - Muhammad Yunus, Zainal Abidin (2013)
Papain is one of the proteolytic enzymes found in the latex of the leaves and of the green fruit of the papaya tree (Carica papaya L.).It’s known to be highly used in the several industry like food,medical,brewing and many more. Hence,the objective of this research is to study the stability of papain in aqueous organic solvent and secondly to purify the papain using the AmberliteTM XAD7HP as the reverse phase liquid chromatography adsorbent.The research is based on experimental lab research.The effects of different concentrations of the water-miscible organic solvents acetonitrile and ethanol on the stability of papain in aqueous solution were studied.Batch adsorption using AmberliteTM XAD7HP was carried out to purify papain from papaya juice.The purified papain was analysed using the Bradford assay,the proteolytic papain activity assay and SDS PAGE.As for conclusion the of the study.The result obtained proved that papain has exhibited higher stability in aqueous acetonitrile than in ethanol under small margin.Decreases in the activity of the enzyme were observed at organic solvent concentrations above 60%.Papain with high purity was achieved by adsorption using the AmberliteTM XAD7HP.